Project Base Learning Analysis In Simple Machine Material In Limited - Christiani, Maria Faeka; Jumadi, Jumadi; Latifah, Yetty (Universitas Ahmad Dahlan, 2023)
Based on the Instruction of the Governor of the D.I. Yogyakarta No. 28/INSTR/2021 to overcome the COVID pandemic, learning is carried out in the form of limited face-to-face meetings. Amount students who are allowed to attend is 30%, and the others studied outside, that used google classroom. Currently, class VIII students have not interacted directly friends or educators for 15 months since entering school. This is indicated by the level of activity in answering questions of 13.6%. This research is a qualitative research that analyzes the project base learning method in the topic of simple planes in limited face-to-face meetings. PjBL steps 1) Formation of groups in project activities. 2) Presenting real-world problems, applying a simple machine in cardboard machine, 3) Making a project work schedule requires the educator role. Educator supervision determines the success rate of project creation. 4) Problem findings are discussed and consulted educators directly and used whatts app groups. 5) The product exhibition is held in the physics laboratory. 6) The maturity level of students determines the dependence of mentoring. The 21st century capabilities that can be achieved in the application of PjBL through communication and collaboration as well as metacognitive abilities. Metacognition in the form of the ability to set learning goals, monitor the execution of knowledge, clarity and accuracy. Weaknesses in communicating due to limited face-to-face meeting conditions, substituted with whats app groups for discussion